Effect of Sakura Block on Milk Production and Milk Quality of FH Cows in Late Lactation - Jarmuji Jarmuji; D. Suherman; Yanuri Yanuri; R. Afriansyah; E. Sulistyowati (Universitas Bengkulu, 2021)
This study aims to evaluate milk production, fat content, and protein content of Friesian Holland (FH) dairy cow's milk by giving Sakura block at the final lactation of FH cow. The design used was the Latin Square Design (LSD), with treatments of P0 (0 Sakura blocks), P1 (300 gr Sakura blocks), P2 (600 gr Sakura blocks), and P3 (900 gr Sakura blocks). This study involved four dairy cows for four periods of which period consisted of 10 treatment days, where the last 3 days of each period were the milk sample collection. Milk production and feed consumption were measured and weighed daily. The results showed that the treatment had a significant effect (P <0.05) on the consumption of dry matter ratio and no significant effect (P> 0.05) on milk production, fat content, and milk protein.